Redefining TVET Leadership in Kenya: A Case for Transition from VNR to VLR and the Integration of Indigenous Philosophies - Matu, Jeffrey; Rothwell, William (Nordic Journal of Comparative and International Education (NJCIE), 2024)
The alignment of technical and vocational education and training (TVET) with industry needs is pivotal for achieving sustainable development goals (SDGs) in Kenya. Yet, reliance on global commitment mechanisms, primarily voluntary national reviews (VNRs), has proven insufficient. This forum piece argues for a strategic transition towards voluntary local reviews (VLRs) and incorporating indigenous philosophies, such as Harambee, to better align TVET with SDG objectives. This transition is essential for fostering inclusive, equitable learning environments, enhancing workforce preparedness, and facilitating a community-centric educational model that effectively addresses local needs while contributing to global sustainability goals. Additionally, this forum piece underscores the need for institutional social change to resolve contradictions in current policies that hinder educational systems from reaching their goals. Drawing from a comparative study of TVET governance models in Nairobi, Kenya, and Pittsburgh, USA, this forum piece illustrates how different approaches can align TVET systems with localized educational demands and SDG frameworks, highlighting policy innovation, leadership development, and community engagement as key strategies for redefining TVET leadership.